LOVEBIRD BIRD DISEASE DIAGNOSIS EXPERT SYSTEM - Yuli Cahyo Nugroho; Fiqih Satria (SRA Publishing, 2021)
Lovebird birds are one of the chirping birds that are being favored by the public today, apart from their melodious voice and beautiful color patterns. not a few breeders want to try to breed this type of bird, but some breeders who are just starting out tend to not understand what types of diseases can attack lovebirds. Farmers can even lose from this. Therefore, an expert system for diagnosing the disease of lovebird birds was created. The expert system for diagnosing lovebird birds is designed with a web-based application, while in the design it uses a Software Development Life Cycle, by taking a sample of the disease, namely dancing disease and with this disease diagnosis expert system it is hoped that it can help breeders know and deal with lovebirds that are affected by the disease. and also the percentage of results that are likely to occur will also be displayed in this expert system.